Preparation of sponge-like activated carbon via carbonization of super absorbent polymer (SAP) as electrode materials for supercapacitors. Issue 10 (2nd October 2016) - Wu, Jie; Tao, Keyu; Kang, Litao; Jiang, Haiwei; Zhang, Ding; Xu, Shoudong; Wang, Baocheng
ABSTRACT: Sponge-like activated carbon with hierarchical pores and 3-dimensional (3D) connected skeletons has been fabricated by direct carbonization of super absorbent polymer followed by KOH activation. The pore size and shape of the porous carbon could be modulated by variation of carbonization temperature, which significantly affected the electrochemical performance. Specifically, the porous carbon obtained at an activation temperature of 700°C shows excellent capacitive performance in 1M KOH aqueous electrolyte: a high specific capacitance of 243 F/g at a current density of 1A/g, and a high capacitance retention of 95% after 5000 cycles.